The electrochemical facetting of metal surfaces : Preferred crystallographic orientation and roughening effects in electrocatalysis - Triaca, Walter Enrique (1990)
New electrochemical procedures to develop highly rough and preferentially oriented surfaces at face-centered cubic metals are described. The structure and morphology of the different surfaces have been studied through scanning electron and scanning tunneling microscopy. The mechanisms of the processes involved in the development of roughening and preferred crystallographic orientation are discussed on the basis of electrochemical data for platinum in acid electrolytes. The electrochemical behaviour of the new electrode surfaces has been tested for different reactions, such as the electro-oxidation of adsorbed carbon monoxide on preferentially oriented platinum and the adsorption and electrooxidation of both ethylene and reduced carbon dioxide on electrodispersed platinum.